The Relationship Between Material Knowledge About Child Nutrition and Stunting at The Age of 0-5 Years - Mahariah Mahariah; Lya Liestary; Priska Dwi Jayanti; Indah Syahfitri Nasution; Mira Ananda Putri (Journal of Development Research, 2022)
Stunting is a problem that is found in many developing countries, especially in Indonesia. Stunting is a condition of failure to thrive in children caused by chronic malnutrition so that children are too short for their age and have a risk of intellectual decline and an increased risk of degenerative diseases in the future. The purpose of this study was to determine the relationship between maternal knowledge about child nutrition and the incidence of stunting in children aged 0-5 years in Kelambir Village. This study used correlation analytical design with cross sectional approach. The population in this study was all parents who had stunted children aged 0-5 years. The sample was obtained using random sampling, which was as many as 90 people. The instrument used in this study was a questionnaire. The results showed that most respondents had good knowledge about stunting, which was 57 respondents (63.3%). There is a significant relationship between maternal knowledge about stunting and nutrition of children aged 0-5 years in Kelambir Village, Pantai Labu District in 2022. Suggestion: Health education is very important in order to increase maternal knowledge about stunting and the importance of knowing nutrition in children aged 0-5 years.